Supporting Equity and Inclusion of Deaf and Hard-of-Hearing Individuals in Professional Organizations - Huyck, Julia Jones; Anbuhl, Kelsey L.; Buran, Brad N.; Adler, Henry J.; Atcherson, Samuel R.; Cakmak, Ozan; Dwyer, Robert T.; Eddolls, Morgan; El May, Fadhel; Fraenzer, Juergen-Theodor; Funkhouser, Rebekah; Gagliardini, Mathilde; et al. (Frontiers in Education, 2021)
Disability is an important and often overlooked component of diversity. Individuals with disabilities bring a unique perspective to science, technology, engineering, mathematics, and medicine (STEMM) because of their unique experiences approaching complex issues related to health and disability, navigating the healthcare system, creatively solving problems unfamiliar to many individuals without disabilities, managing time and resources that are limited by physical or mental constraints, and advocating for themselves and others in the disabled community. Yet, individuals with disabilities are underrepresented in STEMM. Professional organizations can address this underrepresentation by recruiting individuals with disabilities for leadership opportunities, easing financial burdens, providing equal access, fostering peer-mentor groups, and establishing a culture of equity and inclusion spanning all facets of diversity. We are a group of deaf and hard of hearing (D/HH) engineers, scientists, and clinicians, most of whom are active in clinical practice and/or auditory research. We have worked within our professional societies to improve access and inclusion for D/HH individuals and others with disabilities. We describe how different models of disability inform our understanding of disability as a form of diversity. We address heterogeneity within disabled communities, including intersectionality between disability and other forms of diversity. We highlight how the Association for Research in Otolaryngology has supported our efforts to reduce ableism and promote access and inclusion for D/HH individuals. We also discuss future directions and challenges. The tools and approaches discussed here can be applied by other professional organizations to include individuals with all forms of diversity in STEMM.